The Commonwealth of Dominica: Education sector survey; An analysis of the education and training system and recommendations for its development - Taylor, W. L. (UNESCO)
This volume presents the findings of a sector study mission of UNESCO's Division of Educational Financing, which visited Dominica between 18-22 May, 1981. Its purpose was to identify areas of education and training that could be incorporated in the financing arrangements with external agencies, particularly the World Bank. In addition to numerous tables and statistics giving a profile of the educational system, the report contains a description and analysis of the general educational system, technical and vocational education, agricultural education, and nonformal adult education, with recommendations for each
Keywords: Mission reports